The relationship between computed tomography‐derived sarcopenia, cardiopulmonary exercise testing performance, systemic inflammation, and survival in good performance status patients with oesophago‐gastric cancer undergoing neoadjuvant treatment. Issue 1 (12th December 2022) - McGovern, Josh; Delaney, Jenna; Forshaw, Matthew J.; McCabe, Gerard; Crumley, Andrew B.; McIntosh, David; Laird, Barry J.; Horgan, Paul G.; McMillan, Donald C.; McSorley, Stephen T.; Dolan, Ross D.
Abstract: Background: Thought to capture the nutritional and functional reserve of the cancer patient, whether the computed tomography (CT)‐derived sarcopenia score (CT‐SS) has complimentary prognostic value to commonly utilized pre‐treatment host assessments in patients with oesophago‐gastric (OG) cancer is unknown. The aim of the present study was to examine if the CT‐SS can stratify survival in OG cancer patients with good performance status [Eastern Cooperative Oncology Group Performance Status (ECOG‐PS) 0/1]. Furthermore, if the CT‐SS had complimentary prognostic value to cardiopulmonary exercise testing (CPET) performance and systemic inflammation. Methods: Consecutive patients with confirmed OG cancer and good performance status, who received neoadjuvant chemotherapy (NAC) with a view to surgical resection with curative intent, between 1 January 2010 and 31 December 2015, within NHS Greater Glasgow and Clyde (NHSGGC) and NHS Forth Valley (NHSFV), were identified from a prospectively maintained database. CT‐SSs were grouped as 0/1/2. CPET variables recorded included VO2 anaerobic threshold (AT) and peak. Systemic inflammatory response was determined by modified Glasgow prognostic score (mGPS) and neutrophil/lymphocyte ratio (NLR). Associations between categorical variables were examined using χ 2 test and binary logistics regression analysis. Results: A total of 232 patients met the inclusion criteria. 75% ( n = 174) of patients were male, 54% ( n = 126) were 65 years or older, and 60% ( n = 139) were overweight [body mass index (BMI) ≥25 kg/m 2 ]; 33% ( n = 77) of patients had CT‐SS ≥ 1, 36% ( n = 83) had a low VO2 AT (≤11 ml/kg/min), and 57% ( n = 132) had a low VO2 peak (≤19 ml/kg/min). Of the 200 patients who had pre‐NAC bloods facilitating calculation of the mGPS, 28% ( n = 55) had mGPS ≥ 1. Of the 211 patients who had pre‐NAC bloods facilitating calculation of NLR, 38% ( n = 80) had an NLR ≥ 3; 82% ( n = 190) and 53% ( n = 122) were alive at 1 and 3 years post‐NAC, respectively. On univariate analysis, CT‐SS was significantly associated with sex ( P < 0.05), histological cell type ( P < 0.05), low VO2 AT ( P < 0.05), low VO2 peak ( P < 0.05), BMI ( P < 0.05), mGPS ( P < 0.05), and 3‐year survival ( P < 0.05). On multivariate analysis, tumour, node, and metastasis (TNM) stage ( P < 0.05) and CT‐SS ( P < 0.05) remained significantly associated with 3‐year survival. CT‐SS was significantly associated with 3‐year survival in patients who had mGPS 0 ( P < 0.05), but not low VO2 AT ( P = 0.066) or peak ( P = 0.065). Conclusion: The CT‐SS would appear to capture the nutritional and functional reserve of the patient and is a useful objective measure for stratifying long‐term survival in patients with good performance status undergoing potentially curative treatment for OG cancer.